DETERMINANTS OF PRECANCEROUS CERVICAL LESIONS IN FEMALE SALTED FISH ARTISANS - Lusi Andriani; Zamharira Muslim; Sri Yanniarti; Agnestya Nurul Fergita (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Cervical cancer is the second leading cause of death in women, with 36,633 cases or 9.2% of total cancer cases. Risk factors for cervical cancer include age, age at first marriage, duration of hormonal contraceptive use, parity, smoking, family history of cancer, unhealthy diet, exposure to hazardous substances, and unhealthy lifestyle. The aim of this study was to determine the factors contributing to the incidence of precancerous cervical lesions in women who work as salted fish artisans. A cross-sectional study was conducted involving 70 women who work as salted fish artisans in the Padang Serai Community Health Centre working area who met the criteria. Data were obtained through questionnaires and VIA (Visual Inspection with Acetic Acid) tests. The results showed that 51.4% were under 20 years old and over 35 years old, 55.7% were married under the age of 20, 64.3% were multiparous, 77.1% had used and were currently using hormonal contraceptives, 57.1% had used hormonal contraceptives for more than 2 years, 96.8% did not smoke, 80% of the respondents' husbands or family members smoked, 98.6% had no history of cancer in their families, 98.6% consumed processed salted fish, 100% had negative formalin test results, and 8.6% had precancerous cervical lesions. Variables associated with the occurrence of precancerous cervical lesions were age with a p-value of 0.025 and duration of hormonal contraceptive use with a p-value of 0.034. It is recommended to provide continuous education to women about the dangers of cervical cancer, motivate them to undergo early detection of cervical cancer, maintain vulvovaginal hygiene, and use contraceptives rationally.